The influence of social networks within sports teams on athletes' eating and exercise psychopathology: A longitudinal study. (January 2021) - Scott, Charlotte L.; Haycraft, Emma; Plateau, Carolyn R.
Abstract: Teammates have been found to have an impact on athletes' eating and exercise psychopathology via multiple influence mechanisms (e.g., modelling, making critical comments). However, far less is known about the role of the team social network (i.e. the pattern and strength of relationships between teammates). This novel longitudinal study aimed to explore how athletes' eating and exercise psychopathology becomes more (convergence) or less (divergence) similar to their teammates' over time and to explore how this varies for male and female athletes. A second aim was to identify the role of team social network variables (e.g., popularity) in determining individuals' levels of eating and exercise psychopathology. Athletes (N = 199, mean age 18 years, n  = 123 female) from 20 teams/training groups completed a survey regarding their teammate relationships and eating/exercise psychopathology (Eating Disorder Inventory-2; Athlete Compulsive Exercise Test) at three time points over a 7-month period. Significant interaction effects between time and gender were noted for athlete team variability in eating and exercise psychopathology, where both convergence and divergence of eating and exercise psychopathology was evident. In addition, being well connected to teammates, acting as the bridge between groups of teammates or being part of a cohesive team were longitudinally associated with reduced exercise psychopathology. Disordered eating and exercise prevention strategies should look to harness the behavioural convergence effect demonstrated here, by encouraging healthy eating/exercise practices among teammates. Furthermore, coaches should foster cohesive teammate relationships and be aware of how an athlete's social positioning within their team may affect their susceptibility to exercise psychopathology. Highlights: Team variance in eating and exercise psychopathology changed over the season. Changes in eating and exercise psychopathology differed for male and female teams. Being well connected to teammates was associated with reduced disordered exercise. Being part of a cohesive team was associated with reduced disordered exercise. Developing cohesive teams may be important in preventing disordered exercise.